A critical review of compensation converters for capacitive power transfer in wireless electric vehicle charging circuit topologies - Mohammad Amir; Izhar Ahmad Saifi; Mohammad Waseem; Mohd Tariq (Green Energy and Intelligent Transportation)
The compensation circuit plays a crucial role in the framework of Capacitive Power Transfer (CPT) in wireless Electric Vehicle (EV) charging schemes. Various wireless charging factors such as power transfer capacity, efficiency, and frequency depend on the design of compensation circuit topology. In CPT, power is transferred between the two capacitor plates (one transmitter plate embedded on the track and the other plate which is inserted in the wireless EV chassis operates as a receiver). The transmitter plate is excited by a high frequency source and power is transferred between the plates through an electric field. This review paper introduced an experimental prototype of the Corbin Sparrow (CS), featuring an onboard battery charger and an off-board DC charging port. Additionally, it presented a novel conformal bumper-based approach, highlighting its distinct advantages compared to alternative charging methods. The major challenges to employing capacitive technology in transferring power up to kW level are-the greater air gap between the capacitor of vehicle chassis & ground and the high value of electric field strength in the contour of plates. Also, due to the low value of coupling capacitance, there is the requirement for suitable gain and compensated network which is a major area of concern. This review paper proposed various designs of compensation circuit topologies to achieve the effectiveness of the CPT scheme for Wireless Power Transfer (WPT) systems.